Central banks' response to inflation, output gap, and exchange rate in Nigeria and South Africah - Olusegun Vincent (Cogent Business & Management, 2021)
In Africa, a number of countries like South Africa have adopted inflation targeting. In Nigeria, different monetary policy regimes have been adopted over the years with rather unsatisfactory success. This study examines inflation targeting in Nigeria and South Africa, using fully modified least square to estimate a modified Taylor rule for the period 1970 to 2016. The study unravels evidence of a significant response of inflation and squared inflation to policy interest rates in South Africa, but not in Nigeria. Overall, South Africa's central bank places much emphasis on inflation targeting in setting interest rates, which Nigeria does not. Further, for South Africa, output gap is significant, while it is not significant for Nigeria. The study also reveals that exchange rate, openness to trade and international reserves play significant roles in central bank policy in both countries. In other words, there is need for central banks to adopt an eclectic approach, setting the monetary policy rule to adjust to any observed disequilibrium between output gap, inflation, exchange rate, foreign reserves and openness to trade.
Keywords: E00; E04; E43; F00; G12; G17; 650; Central bank; Exchange rate; FM-OLS; Inflation; Inflation targeting; Monetary policy; Output gap; Taylor rule